A comparison of clinical guidelines, treatment characteristics and outcomes in small cell lung cancer between East Asia and Europe/North America - Chiang, Chi-Lu; Soo, Ross Andrew; Mok, Tony; Voon, Pei Jye; Thamlikitkul, Lucksamon; Cheng, Ying; Horinouchi, Hidehito; Cho, Byong Chul; Xu, Krista Lin; Ahn, Myung-Ju (Frontiers in Oncology, 2025)
Small cell lung cancer (SCLC) is an aggressive neuroendocrine carcinoma with a poor prognosis and accounts for approximately 11% of all lung cancers. Owing to the complex and aggressive nature of the disease, clinical management of SCLC is challenging. Many SCLC regional guidelines, including those from East Asia, have been developed in light of potential regional variations in socioeconomic conditions and healthcare infrastructure. However, less is known about the potential implications of the inherent population/regional differences in clinical management and the emerging treatment landscape in SCLC. Here, we review variations in the real-world patient characteristics and in diagnosis and treatment guidelines in SCLC between East Asia and Europe/North America. We also consider similarities and differences in real-world treatment patterns, as well as clinical outcomes between regions, to explore the need to adapt clinical management in SCLC.